The social adjustment of patients with schizophrenia: implications to the mental health policy in Brazil - Paulo R. Menezes; Anthony H. Mann (Universidade de São Paulo, 1993)
A sample (n=124) of schizophrenic patients from a defined catchment area of the city os S.Paulo, Brazil, who had been consecutively admitted to hospital, was assessed for psychopathological status and social adjustment levels. Sociodemographic, socio-economic and occupational characteristics were recorded: almost 30% of the subjects had no occupation and received no social benefit, more than two-thirds had a monthly per capita income of US$ 100.00 or less. Sixty-five percent presented with Schneiderian firstrank symptoms. Nearly half the sample showed poor or very poor social adjustment in the month prior to admission. The most affected areas of social functioning were participation in the household activities, work and social withdrawal. The current mental health policy of promoting extra-mural care as an alternative to the previous hospital-based model will then mean the investment in a network of new community-based services, that give effective treatment and support to patients and their families. The need of further research into the current picture of mental disorders in the country is stressed.